Molecular Mechanism Underlying the Action of Zona-pellucida Glycoproteins on Mouse Sperm - Balbach, Melanie; Hamzeh, Hussein; Jikeli, Jan F.; Brenker, Christoph; Schiffer, Christian; Hansen, Jan N.; Neugebauer, Pia; Trötschel, Christian; Jovine, Luca; Han, Ling; Florman, Harvey M.; Kaupp, U. Benjamin; et al. (Frontiers in Cell and Developmental Biology, 2020)
Mammalian oocytes are enveloped by the zona pellucida (ZP), an extracellular matrix of glycoproteins. In sperm, stimulation with ZP proteins evokes a rapid Ca2+ influx via the sperm-specific, pH-sensitive Ca2+ channel CatSper. However, the physiological role and molecular mechanisms underlying ZP-dependent activation of CatSper are unknown. Here, we delineate the sequence of ZP-signaling events in mouse sperm. We show that ZP proteins evoke a rapid intracellular pHi increase that rests predominantly on Na+/H+ exchange by NHA1 and requires cAMP synthesis by the soluble adenylyl cyclase sAC as well as a hyperpolarized membrane potential set by the spem-specific K+ channel Slo3. The alkaline-activated CatSper channel translates the ZP-induced pHi increase into a Ca2+ response. Our findings reveal the molecular components underlying ZP action on mouse sperm, opening up new avenues for understanding the basic principles of sperm function and, thereby, mammalian fertilization.